Perceptions of Academicians Towards Performance Appraisal in a Malaysian Public University - Hassan, Roshidi (2005)
Performance appraisal has received much attention from researchers for more than seven decades and dissatisfaction with the appraisal is a common survey finding (Cardy, 1998). Previous research findings mentioned dissatisfaction as one of the most common findings in many organizations, and this issue is no exception in the Malaysian public sector scenario. Ever since its introduction in 1993, the appraisal system has been facing with various problems especially those related to the implementation aspect and had aroused serious concern and mix feelings among the public s&tor employees. Therefore, this study attempts to investigate the employees' perceptions and views on the underlying elements behind their negative perceptions and dissatisfaction toward performance appraisal implementation, the implications of such perceptions on the employees work attitude and finally soliciting their views and suggestions on enhancing the acceptance of the appraisal system. The finding of this study is hoped to assist the government and the management of other public universities in Malaysia to understand better on the complexity and specific problems associated with the implementation of performance appraisal in the public sector especially in the higher learning institutions. Employees' views and their needs and criteria for an acceptable system could become a very important milestone for the government to ponder when planning to introduce a new appraisal system in the future. The input from this study is also hoped to assist the government and public organizations to develop and implement a more reliable, fair, acceptable and effective performance appraisal system in the future. A qualitative research method was used in the study. The primary data for the study was obtained from the semi-structured questions used during the in-depth interviews with the participants, while the secondary data was obtained from various government publications, circulars and participants own documents. It was during the interviews that the participants' feelings and opinions toward performance appraisal were captured. The participants for the interview were sampled using purposive and snowballing techniques. Within the interview duration period, a total of 12 participants' responses to multiple questions related to performance appraisal were obtained as the data was found saturated. Their views on the issues were captured and carefully analyzed by the researcher using qualitative technique underlined in the literatures. The participants in the study were purposefully selected. They comprised of academicians with more than 10 years experience as academician in the public university and as an appraisee. They were purposely sampled because the researcher categorized them as 'information rich' individuals that could help provide useful and detail information on the issues under study. Academicians were selected to be the participant for the study because of the unique nature of their job, they were usually the recipient of the 'imposed' system, highly qualified professionals and whom researcher believed able to provide critical opinion and open discussion on the issues under investigation. The data obtained from the interviews was carefully transcribed, coded, and analyzed using the steps recommended by the literatures. A narrative-style of thick descriptions was used to report the research findings.The study revealed that the academicians were dissatisfied with how performance appraisal was implemented in the organization. They feel that performance appraisal was not properly implemented and do not seem to help them in any way to improve their job performance or personal development. They perceived performance appraisal as just another mechanism for the appraisers to reward the employees of their choice or preference. The process and spirit of implementing a fair appraisal was absent and appraisal is said to be conducted by appraisers in a manner that totally deviated from the expected process and procedures. The weaknesses in performance appraisal implementation had somewhat caused academicians to develop negative perceptions and attitudes toward their job and the overall appraisal system. They were in the opinion that not much can be done by the appraisal system to improve their work performance as most of their suggestions and requests for professional training and development programs were not seriously considered by the management. There were several distinct elements mentioned by the participants that tend to 'disturb' their full acceptance and satisfaction of the appraisal system. Elements related to appraiser competence and biasness, clarity of performance standards, feedback, goal setting session, sufficiency of rewards allocation and training were highlighted during the interviews.Appraiser competence and biasness, closed reporting system, minimal feedback and the absence of clear goals were some of the flaws in implementing performance appraisal which were mentioned by the participants. Despite the dissatisfaction with the implementation of the performance appraisal, some academicians cited satisfaction with the incentives and the amount of monetary and non-monetary rewards that were allocated for excellent performers. They were glad that the government had introduced the appraisal system to measure and reward employees work performance. They felt that performance appraisal had managed to let them know their level of performance and their boss perceptions toward them through their appraisal scores. These two elements had actually saved the system from being totally perceived as a system with little or no benefit at all to employees. The study again discovers that the weaknesses in implementing performance appraisal had caused most academicians to have negative feelings and perceptions toward the appraisal system, the management of the organization and the program which the government introduces. Employees' dissatisfaction and resentment toward the system were manifested through the change in their attitudes and behaviours toward their job and the environment. Based on the data accumulated from the interviews, most participants expressed how performance appraisal had reduced their confidence of the system, reduces their level of motivation, make them less concerns of the system and eventually lead to job withdrawal and low morale. There were some valuable suggestions put forward by the participants on how performance appraisal acceptance and satisfaction could be improved. They believed that employee acceptance and satisfaction could be enhanced if the performance appraisal process is more transparent, the goals and purpose of appraisal is clearly and well defined, the appraisers are well-trained, rewards are sufficiently distributed, and the instruments used be directed towards measuring performance rather than personality traits. Having these elements included in the process of performance appraisal would reflect the sincerity and commitment of the management to provide employees with a fair system of appraisal. In addition, it was proposed that a special unit to monitor performance appraisal implementation and process be established and should consist those who are well trained, competent, and professional in conducting performance appraisal. This unit is expected to monitor the implementation and finally normalize any appraisal discrepancies that might have been committed by the various departments in the institution. In addition, the use of multi-sources of appraisal was suggested to further help enhance the trust, fairness, satisfaction and acceptance towards the organization appraisal system.